The Role of Vitamin D in Type 1 and Type 2 Diabetes Mellitus - Sutiajaya, Nikita Lestari (GLOBAL HEALTH SCIENCE GROUP, 2024)
Vitamin D deficiency has been associated with decreased insulin release, insulin resistance, and type 2 diabetes in experimental and epidemiological studies. Animal studies have shown that 1α,25-dihydroxyvitamin D3 (1,25(OH)2D3) stimulates pancreatic cells to secrete insulin. Genetic polymorphisms of vitamin D-related genes may predispose to impaired glycemic control and type 2 diabetes. The aim of this study was to determine the causality of vitamin D to type 2 diabetes. The method used was to search for articles and theories related to vitamin D and diabetes mellitus. Epidemiological studies have shown an association between low serum 25-hydroxyvitamin D3 (25(OH)D3) concentrations and an increased risk of metabolic syndrome and type 2 diabetes. This may be partly explained by increased fat mass. The results of the search for theories and articles indicate that a possible causal relationship between vitamin D deficiency and type 2 diabetes must be proven by randomized clinical trials showing that type 2 diabetes can be prevented or that insulin release and insulin sensitivity can be improved by vitamin D supplementation.